Cardiac Biomarkers for Risk Stratification of Acute Kidney Injury After Pediatric Cardiac Surgery - Greenberg, Jason H. (Ann Thorac Surg, 2020)
BACKGROUND: Children undergoing a cardiac surgical procedure are at increased risk for acute kidney injury (AKI). Novel biomarkers are needed to improve risk stratification of AKI after cardiac surgery. METHODS: We enrolled children aged 1 month to 18 years old from July 2007 to December 2010 undergoing cardiopulmonary bypass. Three United States Food and Drug Administration-approved plasma biomarkers of cardiac stretch, N-terminal pro B-type natriuretic peptide (NTproBNP), inflammation (ST2), or fibrosis (galectin-3), were measured preoperatively and postoperatively within 6 hours of cardiac surgery. All analyses were stratified by age (<2 or ≥2 years old) to account for changing biomarker distributions during childhood and due to a significant interaction between biomarker and age for galectin-3 and NTproBNP (P < .05). RESULTS: Postoperatively, AKI, defined by a doubling of baseline serum creatinine, was diagnosed in 51 of 194 children <2 years and in 28 of 201 children ≥2 years. After multivariable adjustment, for children <2 years, none of the biomarkers were independently associated with AKI, whereas for children ≥2 years, the highest tertile of preoperative galectin-3 and NTproBNP as well as the postoperative galectin-3 and ST2 were associated with AKI. CONCLUSIONS: Preoperative plasma galectin-3 and NTproBNP and the first postoperative galectin-3 and ST2 levels were independently associated with AKI in children ≥2 years old. The performance of cardiac biomarkers after cardiac surgical procedure is affected by age, and research is required to develop biomarkers for children <2 years old.